Examining self-efficacy levels of football referees - Kural, Sercan; Aydin, Faruk; Kural, Sercan (Gdansk Univ Physical Education & Sport, 2021)
Background: This study examined football referees' self-efficacy according to various variables. Material and methods: The sample included 278 football referees (Mean (age)=26.00 +/- 5.72 years) from different classes in the Ankara province. Participants, selected by convenience sampling, completed the Referee Self-Efficacy Scale (REFS). After testing the main assumptions of parametric tests, t-tests and one-way analysis of variance (ANOVA) were used for data analysis. Results: The t-tests revealed no significant difference in gender and education. As for the ANOVA results, there were significant differences in REFS dimensions physical competency, game knowledge, and decision-making in age; game knowledge and decision-making in income; and physical competency and decision-making in the refereeing level. Conclusions: Self-efficacy levels of football referees vary according to refereeing categories, income levels, and age,
Keywords: Football; Referees; Self-Efficacy